2004
DOI: 10.1016/j.ygeno.2003.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Many amino acid substitution variants identified in DNA repair genes during human population screenings are predicted to impact protein function

Abstract: Over 520 different amino acid substitution variants have been previously identified in the systematic screening of 91 human DNA repair genes for sequence variation. Two algorithms were employed to predict the impact of these amino acid substitutions on protein activity. Sorting Intolerant from Tolerant (SIFT) classified 226 of 508 variants (44%) as "Intolerant." Polymorphism Phenotyping (PolyPhen) classed 165 of 489 amino acid substitutions (34%) as "Probably or possibly damaging." Another 9-15% of the variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
172
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(184 citation statements)
references
References 71 publications
4
172
0
4
Order By: Relevance
“…This finding supports results from a previous analysis, which showed that the predicted scores of SNP functionality from the two algorithms are highly associated, with concordance in the predicted impact observed for approximately 62% of the variants [15].…”
Section: Discussionsupporting
confidence: 90%
“…This finding supports results from a previous analysis, which showed that the predicted scores of SNP functionality from the two algorithms are highly associated, with concordance in the predicted impact observed for approximately 62% of the variants [15].…”
Section: Discussionsupporting
confidence: 90%
“…PolyPhen scores (PISC) were designated as probably damaging (2.00), possibly damaging (1.50 -1.99), potentially damaging (1.25 -1.49), borderline (1.00 -1.24) or benign (0.00 -0.99) according to the classification proposed. 20 SIFT predicts the functional importance of amino-acid substitutions on the basis of the alignment of ortholog or paralog protein sequences. SIFT scores were classified as intolerant (0.00 -0.05), potentially intolerant (0.051 -0.10), borderline (0.101 -0.20) or tolerant (0.201 -1.00) according to the classification proposed.…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…SIFT scores were classified as intolerant (0.00 -0.05), potentially intolerant (0.051 -0.10), borderline (0.101 -0.20) or tolerant (0.201 -1.00) according to the classification proposed. 20,21 PolyPhen has been shown to have more than 80% accuracy of predicting deleterious amino-acid changes and the accuracy of SIFT is over 70%. 20 The sensitivity of PolyPhen and SIFT for identifying deleterious mutations in XP genes is 85 and 83%, respectively.…”
Section: Bioinformatics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its role in DNA repair, The APE1 is involved in both BER and regulation of gene expression as a redox co-activator of different transcription factors, such as p53 NF-kB, Myb, HIF-1a, HLF, PAX and AP-1 (Tell et al, 2005).There are a total of 18 polymorphisms had been reported in APE1, but the most extensively studied polymorphism is a T to G transversion, Asp148Glu (rs3136820, T1349G). This polymorphism has shown that the G allele is associated with an increased mitotic delay after exposure to ionizing radiation (Hu et al, 2001;Xi et al, 2004). The polymorphism of APE1(Asp148Glu and -141T/G) has been massive reported in lung cancer and breast cancer, but it rarely studied in NPC.…”
Section: Discussionmentioning
confidence: 99%